Biomarkers and recent advances in the management and therapy of sickle cell disease - Telen, Marilyn J. (F1000Res, 2015)
Although production of hemoglobin S, the genetic defect that causes sickle cell disease (SCD), directly affects only red blood cells, the manifestations of SCD are pervasive, and almost every cell type and organ system in the body can be involved. Today, the vast majority of patients with SCD who receive modern health care reach adulthood thanks to vaccine prophylaxis and improvements in supportive care, including transfusion. However, once patients reach adulthood, they commonly experience recurrent painful vaso-occlusive crises and frequently have widespread end-organ damage and severely shortened life expectancies. Over the last several decades, research has elucidated many of the mechanisms whereby abnormal red blood cells produce such ubiquitous organ damage. With these discoveries have come new ways to measure disease activity. In addition, new pharmaceutical interventions are now being developed to address what has been learned about disease mechanisms.